2012
DOI: 10.1016/j.chembiol.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Polyketide Proofreading by an Acyltransferase-like Enzyme

Abstract: SUMMARY Trans-acyltransferase polyketide synthases (trans-AT PKSs) are an important group of bacterial enzymes producing bioactive polyketides. One difference from textbook PKSs is the presence of one or more free-standing AT-like enzymes. While one homolog loads the PKS with malonyl units, the function of the second copy (AT2) was unknown. We studied the two ATs PedC and PedD involved in pederin biosynthesis in an uncultivated symbiont. PedD displayed malonyl- but not acetyltransferase activity toward various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 56 publications
2
46
0
1
Order By: Relevance
“…Other biosynthetic genes are also present, including two hypothetical acyltransferases, trtAB, one of which could act as a proofreader (14); two putative oxidoreductases, trtGI, which appear to encode proteins for oxygenases, and a putative polyketide cyclase, trtJ (15), which may be involved in the cyclization of compound 1. In addition to the integrated thioesterase (TE) in trtF, which is expected to cause release of the elongated chain, a standalone type II TE, trtH, also is present and is proposed to cause regeneration of misprimed thiolation domains (16).…”
Section: Resultsmentioning
confidence: 99%
“…Other biosynthetic genes are also present, including two hypothetical acyltransferases, trtAB, one of which could act as a proofreader (14); two putative oxidoreductases, trtGI, which appear to encode proteins for oxygenases, and a putative polyketide cyclase, trtJ (15), which may be involved in the cyclization of compound 1. In addition to the integrated thioesterase (TE) in trtF, which is expected to cause release of the elongated chain, a standalone type II TE, trtH, also is present and is proposed to cause regeneration of misprimed thiolation domains (16).…”
Section: Resultsmentioning
confidence: 99%
“…S4) also grouped OocV-AT2 with the stand-alone acyltransferase PedC. A recent study showed that PedC does not exhibit AT activity but possesses acyl hydrolase activity and cleaves acyl groups bound to ACP, suggesting a role in PKS biosynthetic proofreading (65).…”
Section: (Mt-t-t-ks-t-ks-kr-t-ks-t-te-ks-t-c) -Mt-t-t (Modulementioning
confidence: 99%
“…However, a recently identified class of trans-acting AT-like domains have been shown to harbour hydrolytic activity towards acylthioesters 8 . These enzymes, subsequently classed as acyl hydrolases (AH), are distinctly different from AT domains at the sequence level and form a separate clade in a phylogenetic analysis of AT and AH domains from trans-AT PKSs (Fig 1 and S8).…”
mentioning
confidence: 99%
“…These enzymes, subsequently classed as acyl hydrolases (AH), are distinctly different from AT domains at the sequence level and form a separate clade in a phylogenetic analysis of AT and AH domains from trans-AT PKSs (Fig 1 and S8). AH domains have been proposed to act as proofreading enzymes for the PKS by hydrolysing stalled intermediates from the ACP domains of the biosynthetic assembly line 8,9 . In order to fulfil such a role, the AH domains would require a broad substrate specificity for a range of acyl chains.…”
mentioning
confidence: 99%
See 1 more Smart Citation